1952
DOI: 10.1099/00221287-7-1-2-179
|View full text |Cite
|
Sign up to set email alerts
|

The Immunizing Antigens of Erysipelothrix rhusiopathiae. The Role of the L-Antigen

Abstract: SUMMARY : Vaccines were prepared by forniolizing cultures of Erysipelothrix rhusiopathiae and precipitating with aluminium hydroxide gel (AG). Fifty per cent of mice were protected against about a thousand lethal doses. Two (Ru and VYS) of eleven strains yielded highly potent vaccines.Serum in the medium increased the potency of vaccines and for one of the strains liver extract was needed in the medium to give potent vaccines. In general, vaccines protected well against heterologous strains but protection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, treatment with trypsin resulted in the loss of all activity, suggesting the presence of an essential protein or peptide moiety in the protective antigen. In addition, muramidase, which acts upon B-1, 4-glucosidic linkages in glycosamino To compare further the protective antigen present in the 20P fraction to that which has been previously reported (7), the heat stability of the protective activity of the 20P fraction was studied. Samples (20 ml), containing 8 mg of the 20P fraction in 0.05 M sodium phosphate buffer (pH 6.8) were subjected to 1 hr of exposure in water baths at 50, 64, 75, 85, and 95 C. Results of protection tests (Fig.…”
Section: 75mentioning
confidence: 99%
See 3 more Smart Citations
“…However, treatment with trypsin resulted in the loss of all activity, suggesting the presence of an essential protein or peptide moiety in the protective antigen. In addition, muramidase, which acts upon B-1, 4-glucosidic linkages in glycosamino To compare further the protective antigen present in the 20P fraction to that which has been previously reported (7), the heat stability of the protective activity of the 20P fraction was studied. Samples (20 ml), containing 8 mg of the 20P fraction in 0.05 M sodium phosphate buffer (pH 6.8) were subjected to 1 hr of exposure in water baths at 50, 64, 75, 85, and 95 C. Results of protection tests (Fig.…”
Section: 75mentioning
confidence: 99%
“…Samples (20 ml), containing 8 mg of the 20P fraction in 0.05 M sodium phosphate buffer (pH 6.8) were subjected to 1 hr of exposure in water baths at 50, 64, 75, 85, and 95 C. Results of protection tests (Fig. 3) indicated that there was no loss of activity at 50 C. At 64 C, the point at which Gledhill (7) reported that all activity was lost, there was still about 25% of the protective activity present. The protective activity remained at this level through treatment at 85 C but at 95 C again decreased.…”
Section: 75mentioning
confidence: 99%
See 2 more Smart Citations